2016
DOI: 10.1038/cdd.2016.46
|View full text |Cite
|
Sign up to set email alerts
|

RIPK3 deficiency or catalytically inactive RIPK1 provides greater benefit than MLKL deficiency in mouse models of inflammation and tissue injury

Abstract: Necroptosis is a caspase-independent form of cell death that is triggered by activation of the receptor interacting serine/threonine kinase 3 (RIPK3) and phosphorylation of its pseudokinase substrate mixed lineage kinase-like (MLKL), which then translocates to membranes and promotes cell lysis. Activation of RIPK3 is regulated by the kinase RIPK1. Here we analyze the contribution of RIPK1, RIPK3, or MLKL to several mouse disease models. Loss of RIPK3 had no effect on lipopolysaccharide-induced sepsis, dextran … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
426
5
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(452 citation statements)
references
References 59 publications
19
426
5
2
Order By: Relevance
“…Inflammation driven by necroptotic signaling is not necessarily dependent on MLKL killing, but can instead be caused by activation of RIP kinases (42) or through MLKL-activation of NLRP3, driving cytokine secretion (17)(18)(19). Our results indicate that MLKL-induced NLRP3 activity and IL-1β secretion, not necroptotic DAMP release, is the dominant activator of NF-κB signaling in healthy bystander cells.…”
Section: Discussionmentioning
confidence: 76%
“…Inflammation driven by necroptotic signaling is not necessarily dependent on MLKL killing, but can instead be caused by activation of RIP kinases (42) or through MLKL-activation of NLRP3, driving cytokine secretion (17)(18)(19). Our results indicate that MLKL-induced NLRP3 activity and IL-1β secretion, not necroptotic DAMP release, is the dominant activator of NF-κB signaling in healthy bystander cells.…”
Section: Discussionmentioning
confidence: 76%
“…Although necrosis is observed in a variety of pathophysiological processes, traditional necrosis is considered unregulated. However, recent studies have confirmed the characteristics of necrosis, known as necroptosis in mouse models of inflammation and ischemia-reperfusion injury [98]. Necroptosis is a form of programmed cell death that is controlled by death signals and displays a death pattern like that of necrosis [98].…”
Section: Necrosis and Necroptosismentioning
confidence: 99%
“…However, recent studies have confirmed the characteristics of necrosis, known as necroptosis in mouse models of inflammation and ischemia-reperfusion injury [98]. Necroptosis is a form of programmed cell death that is controlled by death signals and displays a death pattern like that of necrosis [98]. Local ischemia is caused by obstruction of blood flow to tissue, resulting in a limited supply of oxygen and nutrients, which if prolonged, can impair energy metabolism and cell death [99].…”
Section: Necrosis and Necroptosismentioning
confidence: 99%
“…Lactate is released from cells when glycolytic activity exceeds mitochondrial respiration and can occur in hypoxic as well as normoxic conditions (aerobic glycolysis) (7,8). Lactate-producing aerobic glycolysis takes place in the developing brain (9,10), suggesting that lactate signaling could play a role in glial development and neurogenesis (11). Here we have used HCAR1 KO mice, organotypic brain slice cultures, and immunohistochemistry to examine the role of HCAR1 in the development and survival of neurons and oligodendrocytes in normal conditions and hypoglycemia.…”
Section: T03-022bmentioning
confidence: 99%